O PROFMAT e as relações distintivas no campo da matemática - Farias, José Vilani de (Universidade Federal de São Carlos, 2017)
Several national and international studies have addressed the teacher training model in the past decades. A large number of educators, including mathematics teachers, have focused on the theme of mathematics teacher training in Basic Education seeking to discuss, among other topics, the necessary knowledge for teaching practice. In this context, changes in the Brazilian legislation and the institutional support of the government were also observed - factors that fostered teacher training courses with the aim of improving education in the country. The Professional Master's Degree Course in Mathematics (Profmat) is among these initiatives. The Profmat came into force in 2011, having in-service Basic Education mathematics teachers as their target audience. The choice of Profmat as the object of this study is justified because of its size and scope: the number of students enrolled and trained; the number of participating institutions; the Program investment, which exceeds that of other professional master‘s degree courses, including the granting of scholarships. This choice is also justified because Profmat was designed and implemented, and is administered by the Brazilian Mathematical Society (SBM) and the National Institute of Pure and Applied Mathematics (Impa), that is, by professional mathematicians who do not develop research addressing teacher training and do not establish interlocution with researchers in this area. The following questions are posed with reference to studies on teacher training: If the scope of this Program is justified by the need and importance to enhance the ability of teachers in favor of Basic Education, how to justify it if the emphasis of this professional course is in mathematics education aiming more comprehensive knowledge on specific contents and with few disciplines focused on the discussion of educational problems? How to justify the fact that a program with this characteristic - not attending the demands of in-service teachers - become a model for other programs in other areas, such as Physics, Languages, History, etc.? To this end, the theory of Pierre Bourdieu with the concepts of habitus, field, and capital was used. The sociological investigation, based on the notion of mathematics field, allowed the understanding of Profmat as a strategy to value a way of seeing and doing specific mathematics that, owing to its distance from the teaching practice, does not contemplate the specificities and does not meet the needs of teacher practice.
Keywords: Formação de professores; Matemática acadêmica e escolar; Mestrado profissional; Campo da Matemática; Bourdieu, Pierre, 1930-2002; Teacher training; Academic and school mathematics; Professional master's degree; Mathematics field; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS HUMANAS::EDUCACAO